The avenger [videorecording (DVD)] - Fairbanks, Davie; Small, Marc; Kneafsey, Honor, 2004-; Laray, Deji; Harris, Mark (Rising Sun Media Inc., 2025)
Matt Hollis decides to take his wife and six-year-old daughter Lara on a trip of a lifetime to Los Angeles. But Matt's world is turned upside down when his wife is attacked in their holiday home, leaving her in a coma and their daughter Lara kidnapped by a child trafficking ring. Realizing he only has a 72-hour window if he ever wants to see his daughter alive again, he enlists the help of an old ex-special forces buddy. Together they tear a path of bloody vengeance through the streets of L.A.